2010
DOI: 10.5213/inj.2010.14.4.250
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Risk Factors for Impaired Quality of Life in Middle-Aged Women with Urinary Incontinence

Abstract: PurposeUrinary incontinence (UI) has substantial and important impacts on quality of life (QoL). The purpose of this study was to identify the associated risk factors of QoL in middle-aged women with UI.MethodsThe participants were 127 women aged 40-64 years who experienced UI. Data were collected from October to November, 2008 using a self-reported questionnaires. The data were analyzed through t-test, one-way ANOVA, Scheffe test, and multiple linear regression with SPSS ver. 16.0 program.ResultsThe distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…, Monz et al . , Son & Kwon ), the present study found that symptom severity is the most important predictor of QoL, without the consideration of disease stigma. Symptom severity can explain 11·7% the variance in QoL.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…, Monz et al . , Son & Kwon ), the present study found that symptom severity is the most important predictor of QoL, without the consideration of disease stigma. Symptom severity can explain 11·7% the variance in QoL.…”
Section: Discussionmentioning
confidence: 42%
“…Previous studies have found that QoL is correlated with some socio‐demographic and clinical factors, such as age, educational level, comorbidity, symptom severity, UI subtype, duration of UI symptoms, among which symptom severity is the most powerful factor (Son & Kwon , Tincello et al . , Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that women with UI often have a poorer quality of life (QOL) than those without UI [4][5][6]. Symptom severity of UI has the largest effect on QOL [7,8]. Findings from a cross-sectional study of 556 women aged 49-61 years showed that the correlation between symptom severity and QOL persisted even after adjusting for other factors such as age, educational level, and duration of UI [9].…”
Section: Introductionmentioning
confidence: 96%
“…The prevalence of UI in women is reported as 10–60% [2–10] . This wide range of prevalence is due to differences in definitions, study characteristics and target populations [11] .…”
Section: Introductionmentioning
confidence: 99%